Exploring Travel Preferences and Behaviours among Indian Tourists: An Empirical Study of Kolhapur, Maharashtra - Seema Y Maloo; Shakti Prathaban (AG Volumes, 2026)
This research investigates travel preferences and behaviours of Indian tourists visiting Kolhapur, Maharashtra. Utilizing a structured questionnaire and analyzing primary data collected from 300 respondents. The study evaluates tourist demographics, motives, information sources and experience levels. Hypothesis testing explores relationships between age and travel purpose and information source and travel experience. The findings highlight the dominance of online research as an information source, leisure and pilgrimage as principal travel purposes and the significant share of young and middle-aged travellers. The study also offers recommendations for stakeholders in Kolhapur’s tourism sector, based on a quantitative and analytical review of tourist behaviours.